HUBUNGAN PEER ACCEPTANCE DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR SISWA KELAS V SD - Firdatuz Zuhriyah (Jurnal Pendidikan Dasar, 2020)
This research was conduct to describe the correlation between peer acceptance and learning motivation with learning achievement, the correlation between peer acceptance and learning achievement, and the correlation between learning motivation and student achievement in 5th grade in SDN Subdistrict of Klojen, Malang. This research was an ex-post facto by using quantitative approach with correlational methods. The subject of this research was 209 5th grade students taken from 7 elementary schools. The research result: 1) Have a positive and significant correlation between peer acceptance and learning motivation with learning achievement by Fcount 44.885>Ftable 3.039 with a significance level of 5%, and the significance value was 0.000<0.05. An effective contribution of 30%, while the remaining 70% is explained by other variables. 2) Have a positive and significant correlation between peer acceptance and learning achievement by tcount 3.060>ttable 1.972 and the significance value is 0.003<0.05. 3) Have a positive and significant relationship between learning motivation and learning by tcount 4.341>ttable 1.972 and the significance value is 0.000<0.05.